Economic Transformation To Get Out of the Middle Income Trap Condition To Reach Indonesia Gold 2045 - Maryanti, Sri; Widayat, Prama; Lubis, Nurhayani (ADPEBI International Journal of Business and Social Science, 2023)
Objectives – The article aims to analyze whether the Economic Transformation carried out by Indonesia will be able to get Indonesia out of the Middle Income Trap (MIT). And whether through economic transformation is able to realize a Golden Indonesia 2045. Methodology- In this study, the method used is descriptive and literature study where in descriptive analysis data and information will be displayed by comparing several countries that were originally included in middle-income countries such as Malaysia, China and Thailand as well as high-income countries such as Japan and South Korea. The data and information collected are taken from 1970-2021 from various sources. In this study, the method used is descriptive and literature study where in descriptive analysis data and information will be displayed by comparing several countries that were originally included in middle-income countries such as Malaysia, China and Thailand as well as high-income countries such as Japan and South Korea. The data and information collected are taken from 1970-2021 from various sources. Findings – In the short term, Indonesia must accelerate capital accumulation through accelerated investment, especially related to infrastructure, in order to encourage economic growth above 6%. In the medium term, it must develop, utilize innovation and technology in order to increase Total Factor Productivity (TFP). The economic transformation carried out by Indonesia is focused on the triggering factors and 4 (four) "Global Megatrends" otherwise the opportunity to get out of the Middle Income Trap (MIT) condition will take 30 years approximately 2053. Efforts are made by building human resources, strengthening digitalization, improving institutions. Indonesia can get out of the Middle Income Trap (MIT) condition if triggering factors such as export structure, and TFP, innovation and structural (against the background of country-specific characteristics) as shown in figure 8 can be overcome Renewal- In this study, it analyzes the efforts made by Indonesia to get out of the Middle Income Trap condition with the vision and mission of Indonesia Emas 2045. This study explains when Indonesia can get out of the Middle Income Trap.